Problem-Solving Approach In Dawah Communication For Adolescent Development In The Digital Era - Yanti, Yunidar Cut Mutia; Anggrainy, Septy (KOMUNIKA, 2024)
This research aims to analyze the implementation of contemporary dawah communication through a problem-solving approach to address modern adolescent lifestyles in Parerejo Village, Pringsewu Regency. The study employs a qualitative approach with purposive sampling of religious teachers (ustadz) and adolescents aged 15-17. Data collection was conducted through interviews, observation, and documentation, with data analysis involving reduction, presentation, verification, and triangulation. Results show that adolescent lifestyle is influenced by environmental, economic, educational, and technological factors, with the primary issues relating to self-identity and relationships with the opposite sex. Practical problem-solving approaches include (1) enhancing adolescents' cognitive abilities and (2) providing interpersonal communication spaces. Appropriate contemporary dawah communication methods encompass lectures, discussions, exemplary role modeling (uswatun hasanah), and utilization of digital media tailored to adolescents' biological, psychological, and social needs. This research contributes as a reference for adolescents facing modern lifestyles and as a guide for parents in mentoring adolescent children using problem-solving approaches.